Pinneapple peel as adsorbent of typical textile industry dyes - Ardila Ramírez, Carolina; María Palacio, Ángela Maria; Barrera Zapata, Rolando (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this study, the adsorption of a mixture of dyes used in the textile industry on pineapple peels grown in Chocó and Urabá Antioqueño regions was evaluated. The adsorption processes were carried out for different pH conditions, particle size of the adsorbent and contact time between the adsorbents and the contaminant mixture, while other parameters such as the concentration of contaminants (50 ppm), and the amount of adsorbent (150 mg) were fixed according to the literature. It was found that using a pH of 2.1, average particle diameter of adsorbent of 0.6 mm and 8 h of operation, recovery percentages of 59.2 ± 1.9 of dyes with peels from Urabá pineapples and 51.7 ± 2.1 with peels from Chocó pineapples are achieved. Using the same conditions and activated charcoal as adsorbent, the contaminants recovery was 34.1 ± 2.1, which is similar to that achieved when the pineapple peels are recovered and reused two times in the process. According to the results, it is concluded that the use or implementation of pineapple peels as a dye adsorbent represents potential economic and environmental benefits for the agroindustrial sector and the textile industry